2020
DOI: 10.1101/2020.04.17.20068577
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Aerosolized Hydrogen Peroxide Decontamination of N95 Respirators, with Fit-Testing and Viral Inactivation, Demonstrates Feasibility for Re-Use During the COVID-19 Pandemic

Abstract: In response to the current urgent demand for N95 respirators by healthcare workers responding to the COVID-19 pandemic, with particular emphasis on needs within local medical systems, we initiated an N95 decontamination study using aerosolized hydrogen peroxide or aHP (7% H2O2 solution), via the Pathogo Curis® (Curis) decontamination system. The study has thus far included 10 cycles of respirator decontamination, with periodic qualitative and quantitative fit testing to verify ongoing respirator integrity thro… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(25 citation statements)
references
References 52 publications
(178 reference statements)
0
25
0
Order By: Relevance
“…The results from the eight H1N1 results 33,38,63,65 were presented in log reduction ranges, not specific log reductions, which precludes analysis herein. In the eight Phi6 results 27,40,56,72 , moist heat at 72-82°C for 30 minutes achieved <6 or >6 log reduction but inaccurate humidity readings occlude results, 7% aerosolized hydrogen peroxide had >6 log reductions with 30 minute exposure, and VHP at 16 gram/minute had >4 log after 30-40 minute exposure time; please note UVGI for one minute had only 1.5 log reduction. In the six IAV samples 41,43,56,63 , ozone removed 1-2 log after 40 minute exposure to 20 ppm, and moist heat and MGS achieved >3 log reduction after 30 minutes exposure to 60-82C moist heat for 30 minutes and 2 minute exposure to MGS.…”
Section: Mask Disinfectionmentioning
confidence: 95%
See 1 more Smart Citation
“…The results from the eight H1N1 results 33,38,63,65 were presented in log reduction ranges, not specific log reductions, which precludes analysis herein. In the eight Phi6 results 27,40,56,72 , moist heat at 72-82°C for 30 minutes achieved <6 or >6 log reduction but inaccurate humidity readings occlude results, 7% aerosolized hydrogen peroxide had >6 log reductions with 30 minute exposure, and VHP at 16 gram/minute had >4 log after 30-40 minute exposure time; please note UVGI for one minute had only 1.5 log reduction. In the six IAV samples 41,43,56,63 , ozone removed 1-2 log after 40 minute exposure to 20 ppm, and moist heat and MGS achieved >3 log reduction after 30 minutes exposure to 60-82C moist heat for 30 minutes and 2 minute exposure to MGS.…”
Section: Mask Disinfectionmentioning
confidence: 95%
“…Hydrogen peroxide disinfection (n=20) 15,19,27,29,30,36,45,51,57,[59][60][61]68 , dry heat (n=19) 12, 16, 19, 21, 29, 33-35, 42, 45, 49, 50, 52, 54 , UVGI (n=13) 15,16,29,35,42,45,46,52,[59][60][61][62] , and ethylene oxide (n=5) 19,[59][60][61] all had promising results.…”
Section: Mask Reusementioning
confidence: 99%
“…The copyright holder for this preprint this version posted September 3, 2020. ; https://doi.org/10.1101/2020.09.01.20179879 doi: medRxiv preprint reprocessing method: parameter combination. As we write this review, a large body of literature on reprocessing of N95-FFRs has been already published till 30 th June 2020 [44][45][46][47][48][49][50][51][52][53][54][55][56][57][58]. but when we did literature search, only few studies were published [44,45,49,58] and majority were in preprint, non-peer reviewed versions.…”
Section: Variables Of Decontamination Methods Variables Of Ffrs Resultsmentioning
confidence: 99%
“…Multiple studies 7,8,12,13,15,18 have demonstrated that N95 FFRs inoculated with SARS-CoV-2 or other organisms can be effectively inactivated with proper use of decontamination systems that generate vapor from H 2 O 2 . However, dosing protocols are complex and could result in incomplete decontamination.…”
Section: Discussionmentioning
confidence: 99%
“…The only study of HPGP (STERRAD 100NX applied for a standard 47-min cycle) on FFRs (3M 1860S) inoculated with virus found that it inactivated VSV on all cutouts. 6 Derr et al 15 evaluated viral decontamination using the Curis AHP system (room volume 48 m 3 ) on five models of N95 FFRs (3M 1860, 1870+, 8511, 9211+, and Honeywell Sperian N11125) inoculated with herpes simplex virus 1, Coxsackie virus B3, and phage phi6. By the time the treatment had inactivated the biological index (G. stearothermophilus), all viruses were similarly inactivated to >6 log.…”
Section: H 2 O 2 Methods and Inactivation Of Other Organismsmentioning
confidence: 99%